Dietary Practices, Nutrient Adequacy, and Nutrition Status among Adolescents in Boarding High Schools in the Kilimanjaro Region, Tanzania - Nicholaus, Calista (J Nutr Metab, 2020)
A cross-sectional study was conducted to assess dietary practices, nutrient adequacy, and nutrition status among 164 adolescents aged between 16 and 19 years in boarding secondary schools in the Kilimanjaro region. In-depth interviews and a survey guided by a semistructured and structured questionnaire, including 24-hour recall and food frequency questionnaire techniques, were used to collect information. Nutrition status was assessed using anthropometric measurements and hemoglobin levels. WHO AnthroPlus software and NutriSurvey software were used to analyze anthropometry and dietary data, respectively. Diet in boarding schools was monotonous comprising mainly of cereal-legume meal with low intake of animal sources, fruits, and vegetables. Mean intake of energy, vitamin C, iron, calcium, and zinc was 1392 kcal, 24.8 mg, 9.2 mg, 134.5 mg, and 4.3 mg, respectively, which were below the Recommended Daily Allowance. The average carbohydrate, fat, and protein intake of 471.9 g, 73.7 g, and 80.7 g, respectively, were slightly higher than the Recommended Daily Allowance in both sexes. Male had a significantly higher intake of protein and carbohydrates (P < 0.001). Female had a significantly (P < 0.001) high intake of fat compared to male adolescents. Overall, 23.1% of the adolescents were anaemic, 25% were overweight, and 6.1% were obese. Boarding secondary schools' diet is monotonous and are inadequate in key micronutrients, iron, zinc, calcium, and vitamin C. There is a coexistence of undernutrition and overnutrition among adolescents in boarding schools. Therefore, monitoring adolescents' dietary intake and nutrition status is a key in preventing adolescents' malnutrition in the short term and diet-related diseases in the long term.